2020
DOI: 10.20944/preprints202001.0278.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ecosystems Monitoring Powered by Environmental Genomics: A Review of Current Strategies with An Implementation Roadmap

Abstract: A decade after environmental scientists integrated high-throughput sequencing technologies in their toolbox, the genomics-based monitoring of anthropogenic impacts on biodiversity and ecosystems is yet to be implemented by regulatory frameworks. Despite the broadly acknowledged potential of environmental DNA and RNA to cost-efficiently and accurately monitor biodiversity, technical limitations and conceptual issues still stand in the way of its routine application by end-users. In addition, the multiplicity of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 163 publications
(203 reference statements)
0
12
0
Order By: Relevance
“…
Biodiversity studies increasingly use environmental DNA (eDNA)based methods to assess community patterns (Cordier et al, 2020;Dornelas et al, 2019), to discover rare organisms (Jerde et al, 2011), and to detect invasive species (Holman et al, 2019).Comparisons between non-molecular and eDNA biodiversity surveys have consistently shown that eDNA surveys are highly sensitive and can detect species accurately at a reduced cost (Blackman
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
Biodiversity studies increasingly use environmental DNA (eDNA)based methods to assess community patterns (Cordier et al, 2020;Dornelas et al, 2019), to discover rare organisms (Jerde et al, 2011), and to detect invasive species (Holman et al, 2019).Comparisons between non-molecular and eDNA biodiversity surveys have consistently shown that eDNA surveys are highly sensitive and can detect species accurately at a reduced cost (Blackman
…”
mentioning
confidence: 99%
“…Biodiversity studies increasingly use environmental DNA (eDNA)based methods to assess community patterns (Cordier et al, 2020;Dornelas et al, 2019), to discover rare organisms (Jerde et al, 2011), and to detect invasive species (Holman et al, 2019).…”
mentioning
confidence: 99%
“…Regarding the extraction of geographic metadata from NCBI records, the completeness and collection of data can improve drastically the biogeographic and ecological research, allowing not only to explore sampling areas, but also to improve phylogeography investigations, biodiversity monitoring and environmental genomics strategies [12, 47].…”
Section: Extaxsimentioning
confidence: 99%
“…DNA metabarcoding coupled with high‐throughput sequencing is currently revolutionising the way we assess and describe biodiversity across environments and taxa, and is therefore becoming a tool of choice for basic and applied research, as well as for biomonitoring applications (Cordier et al., 2020; Deiner et al., 2017; Taberlet et al., 2018). In recent years, various bioinformatic pipelines and tools have been developed to handle DNA metabarcoding data.…”
Section: Introductionmentioning
confidence: 99%